Aplicación del principio de igualdad en delitos contra la mujer y miembros del núcleo familiar, por los sujetos procesales. - Velasco Carvajal, Darwin Benigno (2022)
This research project addressed a very important issue such as the principle of equality in crimes against women and members of the family nucleus, a principle that is characterized by the fact that in its context it determines that every person without any discrimination will have access to justice. under equal conditions, but the problem addressed around the application of this principle is the disadvantage that develops in the procedural subjects, mainly in the defendant, who apparently has all the guarantees for the development of the criminal process, therefore, through this research project, it has been determined which are those legal loopholes that violate to a certain extent the rights, both of the victim and, more frequently, of the accused. This investigation is justified as relevant, since it constitutes a critical legal document with logical results on the application of the principle of equality in crimes of violence against women and members of the family nucleus, likewise, this investigation will be an important reference, since it will be a reference source to which legal professionals and judicial officials can access to better understand how the principle of equality is applied. This research was developed under a selected methodology, since it was developed under a quantitative approach through which it is possible to capture in the investigative work clear ideas previously verified that are developed by different authors of law, in relation to the types of research that will be developed we have historical research, bibliographic, field and documentary research, while the technique that was used in the development of the research project is the survey technique, one of the most used in this type of research work, since it allowed collecting information in a numerical way that was captured through tables and graphs. Under this preamble, it is established that there is a crime of domestic violence at the moment, regardless of the sex of the victim, and the victim has the right to report the act. However, from that, it is no less true that according to the complaints that are presented in the Judicial Units of Women, Family, Childhood and Adolescence, in the vast majority of them the woman is indicated as a victim and she is provided with protection and assistance. immediately which does not happen when the victim is a man. For such considerations, in the present investigation the inequality in the judgment within the processes of domestic violence is analyzed, since throughout the processing of these processes to be able to show if the treatment of both the victim and the accused has strict adherence to the principle of equality or in turn check if there is inequality when judging these causes. Within the investigation, the principle of equality is analyzed, its conceptualization within the national and international regulations and the international treaties and conventions that Ecuador has ratified with respect to the violence that is exercised against the members of the family nucleus; as well as a brief analysis of the types of intrafamily violence, the development of the procedure for the judgment within the processes of intrafamily violence, the procedural parts, in addition, it deals with the protection measures applicable to the victim in these processes, the preparatory proceedings , culminating with the respective judgment hearing; and, finally, the research project will draw conclusions about the inequality in the judgment within the processes of domestic violence.